1998
DOI: 10.1088/0031-9155/43/3/009
|View full text |Cite
|
Sign up to set email alerts
|

A three-Gaussian fit of phantom scatter correction data

Abstract: The phantom scatter correction factor Sp of megavoltage photon beams can be accurately described using a three-Gaussian fit. The model leads to six parameters, with which Sp(r) is described as a smooth function of the field radius r for beam qualities in the range from 60Co up to 25 MV. The parameters allow Sp values to be calculated at intermediate beam energies and for any field shape. Calculated Sp(X, Y) values for rectangular fields (X, Y) can be subsequently used as reference values to compare with measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…When tissue-phantom ratios (TPRs) are used for dose calculations, one needs the relative phantom scatter correction factors S p (s) as a function of equivalent square field size s at the depth of normalization d N . A model recently proposed by van Gasteren et al (1998) describes S p (r) for circular fields with radius r by a summation of three Gaussian distributions:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When tissue-phantom ratios (TPRs) are used for dose calculations, one needs the relative phantom scatter correction factors S p (s) as a function of equivalent square field size s at the depth of normalization d N . A model recently proposed by van Gasteren et al (1998) describes S p (r) for circular fields with radius r by a summation of three Gaussian distributions:…”
Section: Introductionmentioning
confidence: 99%
“…The six free parameters are determined by fitting S p (r) at a depth of 10 cm for seven photon beams ranging in energy from 60 Co to 25 MV. Van Gasteren et al (1998) showed that the parameters for other photon beams can be interpolated from the results using the quality index (QI), i.e. the ratio of TPRs measured at 20 and 10 cm depths.…”
Section: Introductionmentioning
confidence: 99%